Given and New Information in Barack Obamaâ€™s Remarks: A Syntactic Form Analysis - Herdiana, Herdiana; Hidayat, Didin Nuruddin; Alek, Alek; Husna, Nida (JOLLT Journal of Languages and Language Teaching, 2020)
This study seeks to figure out how certain new and given information as information structure of syntactic forms are revealed in Barack Obamaâ€™s remarks in Jakarta. The study is focused on the beginning parts of Obamaâ€™s remarks, as in that he recalled his childhood memories of staying in Jakarta, Indonesia, for four years. In order to investigate the information structures, we collected the data from digital documents (scripts and videos) of the remark; then, we analyzed the syntactic forms of article â€œaâ€ (indefinite) and â€œtheâ€ (definite) and also the rheme and theme of the script and the video of the remarks using close textual analysis. The results indicate that the uses of these articles construct certain messages whose tones are either distancing, getting close, or neutralizing the speaker against the audience. Furthermore, the information contained in Obamaâ€™s speech reflected the context-awareness of the speaker and also the audience. The speech could also open up further study on (political) critical discourse analysis, as it was delivered in the political contexts between Indonesia and the USA.